Nonlinear compression of temporal solitons in an optical waveguide via inverse engineering. (10th May 2018) - Paul, Koushik; Sarma, Amarendra K.
Abstract: We propose a novel method based on the so-called shortcut-to-adiabatic passage techniques to achieve fast compression of temporal solitons in a nonlinear waveguide. We demonstrate that soliton compression could be achieved, in principle, at an arbitrarily small distance by inverse-engineering the pulse width and the nonlinearity of the medium. The proposed scheme could possibly be exploited for various short-distance communication protocols and may be even in nonlinear guided wave-optics devices and generation of ultrashort soliton pulses.